On the relevance of chaos for halo stars in the solar neighbourhood II - Maffione, Nicolas P.; Grand, Robert J. J.; Springel, Volker; Pakmor, Rüdiger (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. In a previous paper based on dark matter only simulations we show that, in the approximation of an analytic and static potential describing the stron